The architecture of the classical temple of Hera - Pfaff, Christopher A. (Princeton, New Jersey)
xxx, 367 sayfa
Keywords: “The Heraion was the main sanctuary of Argos and is one of the best-preserved Classical sites in the Peloponnese. This series presents detailed and up-to-date analyses of excavations and fieldwork conducted over more than a century. A temple to the goddess Hera existed at the site at least from the 7th century B.C. The Old Temple burnt down in 423 B.C. and was replaced by a New Temple surrounded by other Archaic and Classical structures“ -- Yayıncı.